Power Relations Between Husband and Wife in Interfaith Families in Pancasila Village - Wicaksono, Harto; Khunaefi, Wildan; Rini, Hartati Sulistyo; Arsi, Antari Ayuning; Gunawan, Gunawan; Kurniawati, Dwi Wahyuni; Utama, Aji Prasetya Wahyu; Romadhoni, Asyif Awaludin (Universitas Negeri Semarang, 2025)
Research on interfaith families has largely emphasized legal frameworks and institutional constraints, often portraying them as fragile or conflict-ridden. Less attention has been given to how interfaith households negotiate power and intimacy in daily life, particularly within rural settings where pluralism has long been practiced. This article examines power relations between husbands and wives in interfaith families in Kapencar Village, Wonosobo, Indonesia. The study argues that power in such households is not simply hierarchical but negotiated through everyday practices that generate resilience and cohesion. Using a qualitative case study approach, data were collected through in-depth interviews and participant observation with twelve interfaith families representing Muslim, Christian, Catholic, and Hindu backgrounds. The analysis highlights negotiations across religious transmission, economic collaboration, reproductive decision-making, parenting, and cultural rituals. Findings show that while relations appear egalitarian on the surface, deeper structures reveal ongoing contestation and adaptation that transform potential conflict into stability. This study contributes to family and interfaith scholarship by demonstrating that negotiation is not a deficit but a productive practice sustaining plural households. It redefines interfaith families as microcosms of pluralism and resilience, offering a lens to rethink family studies beyond legal and doctrinal concerns and toward the politics of everyday life.